The origins of the canon of the Hebrew Bible: an analysis of Josephus and 4 Ezra - Ossándon, Juan Carlos (Journal for the study of Judaism / Supplements, 2019)
"In The Origins of the Canon of the Hebrew Bible: An Analysis of Josephus and 4 Ezra, Juan Carlos Ossandón Widow examines the thorny question of when, how, and why the collection of twenty-four books that today is known as the Hebrew Bible was formed. He carefully studies the two earliest testimonies in this regard--Josephus' Against Apion and 4 Ezra--and proposes that, along with the tendency to idealize the past, which leads to consider that divine revelation to Israel has ceased, an important reason to specify a collection of Scriptures at the end of the first century CE consisted in the need to defend the received tradition to counter those that accepted more books"--